As formações nominais em textos sobre racismo e antirracismo: o caso das nominalizações - Waldemar Duarte de Alencar Neto (2018)
This work presents a study on aspects related to Nominalization, based on the theoretical assumptions of Semantics of Enunciation proposed by Guimarães (1995, 2005). Traditionally defined as the process by which one obtains a word from another already existing, this phenomenon is discussed within a perspective that produces, according to Dias (2015c), a look at the language that results in significant differences in the concept of linguistic form and, consequently, in the approach of the articulatory units, conceived as nominal formations. In this way, to understand the enunciative functioning of nominalizations in nominal formations implies searching for the enunciative reasons for the linguistic relations nucleated by a nominalized form, that is, to search for the pertinences that this form acquires in the relation between a current of its use and the references that they situate it historically. Considering a diversified corpus, made up of texts on racism and antiracism, we analyzed the occurrences, demarcating differences between historical references and enunciative pertinences through the work with enunciative networks, and we observe in summary the following: as a qualified linguistic form in the enunciation, nominalization acquires an enunciative pertinence whereas a prior object, configured as a predication of existence, ensures that it is situated in that way, not another, in the statement. As a condensing form of a memory of enunciations by the recurrence of its uses, it is able, in enunciative convergence, to envisage, defining, in some measure, the directions of signification. If, in other perspectives, the effects of deletion are discussed around the nominalization, we take this (syntactic) silence from our point of view as meaningful. At this point in the research, we broaden the enunciative reading of the object by proposing a status of completeness linked to nominalization, but shifting this notion of completeness from the insufficient concepts of complementation and necessity, and turning our attention to the requalification of syntactic places of subject and complement, anchored in the constitutive relation between a material dimension and a symbolic dimension, of enunciative order. In the end, we propose continuous representations that clarify the capacity that nominalizations have to evoke references that will define the modes of production of pertinence in the enunciative event.